Discrepancies Between Beliefs and Behavior: A Prospective Study Into Immunosuppressive Medication Adherence After Kidney Transplantation. Issue 2 (February 2015) - Massey, Emma K.; Tielen, Mirjam; Laging, Mirjam; Timman, Reinier; Beck, Denise K.; Khemai, Roshni; van Gelder, Teun; Weimar, Willem
Abstract : Background: Nonadherence to immunosuppressive medication after kidney transplantation is a behavioral issue and as such it is important to understand the psychological factors that influence this behavior. The aim of this study was to investigate the extent to which goal cognitions, illness perceptions, and treatment beliefs were related to changes in self-reported immunosuppressive medication adherence up to 18 months after transplantation. Methods: Interviews were conducted with patients in the outpatient clinic 6 weeks (T1; n = 113), 6 months (T2; n = 106), and 18 months (T3; n = 84) after transplantation. Self-reported adherence was measured using the Basel Assessment of Adherence to Immunosuppressive Medications Scale Interview. Psychological concepts were measured using the Brief Illness Perceptions Questionnaire, Beliefs about Medicines Questionnaire, and questions on the importance of adherence as a personal goal, conflict with other goals, and self-efficacy for goal attainment. Results: Nonadherence significantly increased over time to 31% at T3. Perceived necessity of medication, perceived impact of transplant on life (consequences) and emotional response to transplantation significantly decreased over time. Participants who reported low importance of medication adherence as a personal goal were more likely to become nonadherent over time. Conclusions: Illness perceptions can be described as functional and supportive of adherence which is inconsistent with the pervasive and increasing nonadherence observed. There appears therefore to be a discrepancy between beliefs about adherence and actual behavior. Promoting (intrinsic) motivation for adherence goals and exploring the relative importance in comparison to other personal goals is a potential target for interventions. Abstract : Patient intentions and actual adherence to medications vary significantly, and true adherence associates closely with sense of health and well-being, which have important implications for education and reinforcement of habits in recipients after transplant recovery. Supplemental digital content is available in the text.